Description of the immature stages of Sigara (Tropocorixa) schadei (Hungerford) (Hemiptera: Heteroptera: Corixidae) - Konopko, Susana Amanda (Zootaxa, 2012)
The egg and the five instars of Sigara (Tropocorixa) schadei (Hungerford) are described and illustrated for the first time. The eggs of Sigara have a very short, basal stalk. The egg of S. schadei has protuberances delimiting small areas on the chorionic surface. The main characters separating the five instars of S. schadei are: the body length and body, head and eye widths; the number of transverse sulcations of the rostrum; the number of setae on the inner surface of the protibiotarsus; the number of long, slender setae on posterior and posterodorsal surfaces of the mesotibia and mesotarsus, respectively; the number of spines on posteroventral surface of the mesotibia; the number of campaniform sensilla on posterior surface of the metatrochanter; the number of spines and swimming hairs on anteroventral and posterodorsal surfaces of the metatarsus, respectively; and the grade of development of the wing pads. Some characters distinguish species or group of species in nymphs of the genus Sigara: the chaetotaxy of the urosternites (instar I); the body length, chaetotaxy of the mesonotum, and number of spines on posteroventral surface of the metafemur, and on posterior and posterodorsal surfaces of the metatibia (instar V).